An investigation into the cellular and molecular signalling events which occur in [Beta]-amyloid-treated cultured cortical neurons - Fogarty, Marie (Trinity College (Dublin, Ireland). Department of Physiology, 2004)
Deposition of β-amyloid around neurons is a neuropathological hallmark of Alzheimer’s disease. The aim of this study was to investigate the cellular and molecular mechanisms underlying β-amyloid-mediated cell death in cultured cortical neurons. β-amyloid evoked a differential timeframe of activation of specific isoforms of the stress- activated protein kinases, c-jun-N-terminal kinase. To delineate the respective roles of c- jun-N-terminal kinase iso forms in β-amyloid-mediated cell death, antisense oligonucleotide technology was used. The results demonstrate that c-jun-N-terminal kinase 1 is the principal isoform involved in β-amyloid-mediated activation of caspase-3 and DNA fragmentation. c-jun-N-terminal kinase 1 also stabilised the tumour suppressor protein, p53, via phosphorylation at serine-15. The p53 inhibitor, pifithrin-a, reduced the β-amyloid-mediated increase in expression of pro-apoptotic Bax, activation of caspase-3, cleavage of the DNA repair enzyme, poly (ADP) ribose polymerase, and subsequent DNA fragmentation, indicating that P-amyloid, at least in part, arbitrates neuronal cell death in a p53-dependent manner. β-amyloid increased Bax and p53 expression at the mitochondria. The increased mitochondrial association of Bax and p53 coincided with release of mitochondrial cytochrome c to the cytosol suggesting that these proteins play a role in β-amyloid-mediated regulation of the mitochondrial membrane. A particularly exciting discovery was the observation that β-amyloid promoted the association of Bax and p53 with lysosomes. The association of these proteins with lysosomes coincided with an alteration in lysosomal integrity. Pifithrin-a attenuated the β-amyloid -mediated increase in cytosolic activity of the lysosomal protease, cathepsin-L, suggesting a novel mechanism whereby p53 may contribute to destabilisation of lysosomal membranes and promote leakage of lysosomal constituents.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin